Effect of acid and alkaline mists on biomass and carbohyhdrate partitioning in French bean (Phaseolus vulgaris) - KLOSEIKO, J; MANDRE, M (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1997 and 1998 to study the effect of acid and alkaline mists on biomass and carbohydrate partitioning in french bean (Phaseolus vulgaris L). The plants were trented with acid or alkaline mists (pH2.3, 3.0, 4.5, 7.0, 9.0, 11.0) in greenhouse. Solutions containing H2 SO4 and HNO3 or Ca(OH)2 were applied to plants once a day for 21 days each application being 50 ml/m. The control plants were exposed to distilled water at pH 5.6. A marked decrease in soluble carbohydrates, starch and hemicellulose contents was observed especially at extreme pH values of misting (at pH 2.3 respectively 42,64 and 83% and at pH 11.0 respectively 48, 60 and 82% of control). Soluble carbohydrates: starch was relatively stable in leaves and roots but rapidly increased in stems at all pH values of the treatment solution. The growth of treated plants did not show significant difference from the control, but the biomass partitioning in plant organs showed changes. The shoot: root dry mass ratio of plants increased slightly in all variants of treatment, except in plants treated with a solution of Ca(OH)2 at pH 7.A strong correlation was found between different carbohydrate fractions and the pH value of the treatment solution in the stem and root.